Improved electrical property of Sb-doped SnO2 nanonets as measured by contact and non-contact approaches - Liu, Hongwei (2013)
This work reports the characterization of antimony doping effects on the electron transportation in SnO2 nanonets via a contact (field-effect transistor) and a non-contact (terahertz time-domain spectroscopy) approach. The doping influence is well demonstrated by the contact method through exploring the output characteristics of the devices. In addition, through the analysis of the terahertz time-domain spectra using Drude–Smith model, the non-contact method provides more precise characterization ascribed to the absence of extra effects such as contact resistance and nanowire–nanowire junction barriers.